EFISIENSI PABRIK KELAPA SAWIT DI INDONESIA - Stephanie, Hanny; Tinaprilla, Netti; Rifin, Amzul (Departmen of Agribusiness, Economics and Management Faculty, Bogor Agricultural University, 2018)
Crude palm oil (CPO) is one of Indonesian agricultural products that are widely developed. CPO is produced by palm oil mills. This research analyzes the efficiency of Indonesian palm oil mills uses 2010 manufacturing industry survey conducted by the Statistics Indonesia. The efficiency analysis is done by using Data Envelopment Analysis (DEA) with production value as the output, and production expenses, labor expenses, other expenses, and fixed capital as the inputs. It is found that 26 out 137 firms are efficient. Based on the capital ownership, foreign firms have the highest average efficiency score. Based on export participation, exporting firms have higher efficiency than non-exporting firms. Based on location, firms that located on other islands have higher efficiency than firms that located on Sumatra and Kalimantan.